Failure investigation of GFRP communication towers. (September 2017) - Prasad Rao, N.; Rokade, R.P.; Balagopal, R.
Abstract: The rapid growth in telecommunication system requires a large number of free-standing and guyed towers. Glass Fiber Reinforced Polymer (GFRP) material is corrosion resistant and light weight with specific gravity one-fourth of steel. In triangular based communication towers gusset plates can be avoided by using GFRP 60° angles for leg members. The failures encountered in the full-scale testing of a 24 m high triangular GFRP communication tower designed by the pultruded profile manufacturer purely based on the properties derived from tensile coupon test results is presented in this paper. The GFRP 60° angles as struts exhibited torsional-flexural buckling mode and the 90° angles failed by flexural buckling. ANSYS Shell 281 layered element used to model the GFRP struts predicted the failure loads closer to the experiments. The GFRP 60° angles as leg members have shown torsional-flexural buckling mode till failure but finally failed by de-bonding of layers in the case of angle sections made of stitched mat and by shearing of the cross section in angles with multi-axial technical fabrics. The 60° angles subjected to compression, exhibited higher strength at a component level compared to the leg member in tower restrained by secondary bracings. The strength and behaviour of GFRP angles with multi-axial technical fabrics (± 45°/90°) are superior compared to the angles with stitched mat. Highlights: Development of GFRP triangular based communication tower using GFRP 60° degree angle sections Design guidelines for GFRP communication tower Failure investigation of GFRP communication tower